105k views
5 votes
Given: F(x) = 5x - 6 and G(x) = x - 4

G -1 F -1 =

(x + 26)/5

-6x + 10

(x + 10)/5

User GSto
by
4.8k points

2 Answers

7 votes

Answer:

1st answer

Explanation:

find inverses

then plug in g^-1(f^-1(x)

User Drizzd
by
4.5k points
0 votes

Answer:

Correct choice is
(x+26)/(5)

Explanation:

1. If
F(x)=5x-6, then you can find the inverse
F^(-1)(x):


y=5x-6,\\ \\5x=y+6,\\ \\x=(y+6)/(5),\\ \\F^(-1)(x)=(x+6)/(5).

2. If
G(x)=x-4, then


y=x-4,\\ \\x=y+4,\\ \\G^(-1)(x)=x+4.

3. Hence,


G^(-1)(F^(-1)(x))=G^(-1)\left((x+6)/(5)\right)=(x+6)/(5)+4=(x+26)/(5).

User Andrew Lambert
by
4.9k points